Bull Spermatozoa Express Receptors For Platelet-Activating Factor - Bosch, Pablo; Roudebush, William; McGraw, Royal; DeJarnette, Mel; Marshall, Clifton; Massey, Joe; Brackett, Benjamin (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; p mso-margin-top-alt:auto; margin-right:0cm; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> <!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; p mso-margin-top-alt:auto; margin-right:0cm; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> <!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Platelet-activating factor (PAF; 1-O-Alkyl-2-acetyl-sn-glycero-3-phosphorylcholine) is a ubiquitous phospholipid that is implicated in the mediation of a wide variety of reproductive processes. To better understand the role of PAF in bovine reproduction, it was designed experiments to: (a) determine whether bull spermatozoa express receptors for PAF and (b) study the effect of exogenous PAF on in vitro sperm physiology (i.e., capacitation, acrosome reaction, motility, and fertilizing ability). Bull sperm express PAF receptor as determined by two approaches: RT-PCR and immunofluorescence. However, exposure of spermatozoa to different concentrations of exogenous PAF (10”“11-10”“6 M) did not affect capacitation, acrosome reaction or motility. Consistent with these findings, coculture of gametes in medium containing increasing concentrations of PAF (1 x 10”“8-8 x 10”“6 M) did not improve in vitro fertilization outcome as measured by percentage of inseminated oocytes reaching 2-cell stage 48 h after fertilization. In contrast, PAF at 8 x 10”“6 M concentration significantly inhibited IVF. In conclusion, although bull sperm have PAF receptors, exposure of bull spermatozoa to exogenous PAF failed to enhance the sperm function parameters measured in this study. Additional studies are warranted to elucidate the biological role of PAF on bull spermatozoa.